2021
DOI: 10.1161/circinterventions.120.009960
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of High-Risk Percutaneous Coronary Intervention Without Mechanical Circulatory Support

Abstract: Background: Recommendations to broaden the use of mechanical circulatory support (MCS) for high-risk percutaneous coronary intervention (PCI) remain controversial with the absence of robust evidence from randomized clinical trials and the risk of device-related complications. This investigation examined whether performing high-risk PCI without elective MCS is feasible and safe. Methods: We performed a single-center, retrospective analysis for patients m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Patients undergoing Impella‐assisted PCI should be treated in high‐volume centres with 24 h availability of cardiac surgery and by multidisciplinary teams of experienced operators, to ensure procedural and long‐term success. Details of the technical aspects of these procedures are beyond the scope of this manuscript and have been recently summarized 30–34 . Here, we focus on three crucial procedural aspects that facilitate Impella‐assisted complex PCI: (i) checklist at catheterization laboratory arrival, (ii) large‐bore access and closure techniques, and (iii) completeness of revascularization.…”
Section: Roadmap Towards a High‐risk Percutaneous Coronary Interventi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing Impella‐assisted PCI should be treated in high‐volume centres with 24 h availability of cardiac surgery and by multidisciplinary teams of experienced operators, to ensure procedural and long‐term success. Details of the technical aspects of these procedures are beyond the scope of this manuscript and have been recently summarized 30–34 . Here, we focus on three crucial procedural aspects that facilitate Impella‐assisted complex PCI: (i) checklist at catheterization laboratory arrival, (ii) large‐bore access and closure techniques, and (iii) completeness of revascularization.…”
Section: Roadmap Towards a High‐risk Percutaneous Coronary Interventi...mentioning
confidence: 99%
“…Details of the technical aspects of these procedures are beyond the scope of this manuscript and have been recently summarized. [30][31][32][33][34] Here, we focus on three crucial procedural aspects that facilitate Impella-assisted complex PCI: (i) checklist at catheterization laboratory arrival, (ii) large-bore access and closure techniques, and (iii) completeness of revascularization. We strongly advocate to develop a checklist to be completed at catheterization laboratory arrival, confirming the patient's informed consent, reviewing patient indications and contraindications, recent laboratory data, and LVEF.…”
Section: Step 3: Percutaneous Coronary Intervention With Impellamentioning
confidence: 99%
“…We read with interest the article by Khalid et al, 1 who reported on the feasibility and safety of high-risk percutaneous coronary intervention (PCI) without mechanical circulatory support. The authors are to be praised for their results (procedural success was observed in 98.2%, while 30-day mortality was only 1.6%).…”
Section: To the Editormentioning
confidence: 99%
“…However, we would like to make several comments and offer a different interpretation of their global study findings. First, the high-risk PCI criteria mentioned by the Interventional Council of the American College of Cardiology 2 and referenced as inclusion criteria by Khalid et al 1 have not been widely adopted or prospectively validated. Second, adherence to such high-risk criteria was not complete, as in the study by Khalid et al 1 acute coronary syndromes (which are associated with higher morbidity and mortality) were excluded.…”
Section: To the Editormentioning
confidence: 99%
“…Among AMI types, the prevalence of non-ST-elevation myocardial infarction (NSTEMI) is increasing compared with that of ST-elevation myocardial infarction (STEMI) 5 6. Moreover, PCI is increasingly being used in high-risk patients, including elderly patients, cardiogenic shock with the use of mechanical circulatory support devices and patients with multiple clinical comorbidities 7–9…”
Section: Introductionmentioning
confidence: 99%